Ferromagnetische Inhomogenitäten zur berührungslosen Bestimmung der Geschwindigkeit und gleisselektiven Position von Schienenfahrzeugen - Spindler, Max (Schriftenreihe / Institut für Mess- und Regelungstechnik, Karlsruher Institut für Technologie, 2021)
Ferromagnetic inhomogeneities along the track serve as landmarks. With these, each track section in the track network can be uniquely identified. In addition to non-contact speed determination, this also provides a track-selective method for determining the absolute position of the rail vehicle.